Identidad de Physalis coztomatl Moc. & Sessé ex Dunal como el coztómatl de Francisco Hernández - Martinez, Mahinda (Instituto de Ecología, A.C., 1994)
Physalis coztomatl Moc. & Sessé ex Dunal is the same species as P. stapelioides (Regel) Bitter, over which it has priority and has to be used for the common shrub of the forests in Mexico. The name of the species comes from the work of Francisco Hernández, and the description is based on a drawing of the Icones Pictorum of Sessé & Mociño.